Orally administered live BCG and heat-inactivated Mycobacterium bovis protect bison against experimental bovine tuberculosis - Nirajan Niroula; Priya Ghodasara; Nelson Marreros; Bailey Fuller; Haley Sanderson; Slim Zriba; Stew Walker; Todd K. Shury; Jeffrey M. Chen (Scientific Reports)
Abstract Bovine tuberculosis (BTB) is an infectious disease of livestock and wildlife species that is caused by pathogenic members of the Mycobacterium tuberculosis complex such as Mycobacterium bovis. Due to the introduction of M. bovis-infected bison in the 1920s, BTB is now endemic in wood bison (Bison bison athabascae) population within the Wood Buffalo National Park (WBNP) in northern Canada. This disease poses a grave threat to the long-term survival of this ecologically and culturally important species and has the potential to cause zoonotic TB and spill over to BTB-free livestock and other bison herds that live in the surrounding areas. Thus, effective BTB control strategies in WBNP bison are urgently needed. To this end, we aerosol challenged young bison with different doses of virulent M. bovis and observed disease-associated delayed-type hypersensitivity, gross lung and lymph node pathology and histopathology, as well as M. bovis burden in target organs, thus confirming the establishment of BTB in challenged animals. We then assessed the safety and efficacy of oral live BCG versus oral heat-inactivated M. bovis (HIMB) given in a homologous prime-boost regimen in bison. While both BCG and HIMB offered protection against BTB, BCG-treated bison thrived more, presented with fewer lung lesions at necropsy and lower burden of virulent M. bovis than HIMB-treated animals. Strikingly, oral HIMB induced almost no delayed-type hypersensitivity to intradermal tuberculin while oral live BCG induced very low sensitivity to tuberculin in bison, indicating their potential as DIVA (differentiating infected from vaccinated animals) vaccines for use in this important wildlife species.